Exploring the effects of visual and literary arts interventions on psychosocial well-being of diverse older adults: a mixed methods pilot study. Issue 3 (2nd September 2021) - Johnson, Julene K.; Carpenter, Tim; Goodhart, Nancy; Stewart, Anita L.; du Plessis, Lindsay; Coaston, Angela; Clark, Kristen; Lazar, Ann; Chapline, Jeffrey
ABSTRACT: Background: Engagement in the arts may have health benefits for older adults. Most research has focused on music and dance; less is known about the benefits of other arts interventions. The purpose of this study was to examine the effects of visual (ceramics and collage) and literary arts (storytelling and writing) on well-being. Methods: We used mixed methods to examine the effects of a 12-week visual or literary arts intervention on well-being. Adults age 55 and over from four housing sites were assigned to start an intervention immediately (intervention) or wait 12 weeks (controls). The study included pre/post-test measures of well-being and focus groups about perceived benefits. Results: Compared to controls, participants in the ceramics intervention had significant improvements in interest in life and mastery, while no changes were observed after the storytelling intervention. Seven psychosocial benefits were identified . Conclusions: Participation in visual and literary arts for older adults was associated with well-being media.